EFFECT OF SOIL ON UPTAKE AND UTILIZATION OF NITROGEN BY OAT (Avena sativa L.) - P. K. Ng`ang`a; K. M. Jezik (Journal of Animal and Plant Sciences, 2014)
Growers seeking an alternative to animal residue based organic nitrogen (N) fertilizers can select among a number of different plant- and industry processed organic fertilizers. However, the effect of soil properties on the N release of these fertilizers has not yet been studied. Therefore, three pot experiments were conducted to investigate the influence of different soils on the N utilization of these fertilizers. Grain legumes (unlabelled and 15N labelled) and industry processed plant residues were applied as fertilizers to oat as a model plant, with the effects being evaluated by the calculation of the apparent N utilisation and, in one case, by the N use efficiency. The N release was influenced by the N content of the fertilizers, with the apparent N utilization and the N use efficiency increasing with increasing N content. In addition, soils modified N utilization by the plants, but this effect was dependent upon the N content of the fertilizers. When the N content was low (pea), the apparent N utilization by oat was significantly higher in the coarse textured soils as compared to the fine textured soils. However, when the N content of the fertilizer was higher, plant N uptake was unaffected by the soils. In an experiment conducted with a wider range of soils, the apparent N utilization of two fertilizers with a medium N content differed between the soils, although the differences were not obviously related to any of the soil texture, soil Corg content, or N mineralization of the unfertilized soil. However, a higher N mineralization from the unfertilized soils was associated with a higher N use efficiency of oat from all tested fertilizers, indicating a positive soil-fertilizer interaction in these soils. It is concluded that none of the soil parameters examined could account in isolation for the variations in the N utilization of the fertilizers in different soils. However, the use of fertilizers with a higher N content are generally recommended for achieving a high N utilization, especially for fine textured soils and soils with a high N release.
Keywords: Oat; Grain legumes; Nitrogen; Soil